2005
DOI: 10.1007/s00125-005-1796-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atenolol on QTc interval lengthening during hypoglycaemia in type 1 diabetes

Abstract: Aims/hypothesis: Hypoglycaemia is associated with heart rate-corrected QT (QTc) interval lengthening on the ECG; this may be important in the pathogenesis of sudden overnight death in young people with diabetes. Since hypoglycaemic QTc lengthening appears to be mediated through the sympathoadrenal response, we tested the hypothesis that beta 1 -blockade will prevent these changes in type 1 diabetic patients and so provide a potential therapeutic intervention. Methods: We studied eight type 1 diabetic adults wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 16 publications
2
21
0
3
Order By: Relevance
“…The changes in TCRT tended to be even more evident in the diabetic patients than those occurring in their healthy counterparts. The changes in TCRT were not associated with changes in the autonomic regulation of heart rate, sympatho-adrenal activation or changes in the potassium level, suggesting that hypoglycaemia as such also exerts an influence on cardiac repolarisation patterns by other In several previous studies [3][4][5][6][7][8][9], a prolonged QT c interval and an increased QT dispersion have been reported during hypoglycaemia. According to earlier studies [10], the most often used formula, i.e.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The changes in TCRT tended to be even more evident in the diabetic patients than those occurring in their healthy counterparts. The changes in TCRT were not associated with changes in the autonomic regulation of heart rate, sympatho-adrenal activation or changes in the potassium level, suggesting that hypoglycaemia as such also exerts an influence on cardiac repolarisation patterns by other In several previous studies [3][4][5][6][7][8][9], a prolonged QT c interval and an increased QT dispersion have been reported during hypoglycaemia. According to earlier studies [10], the most often used formula, i.e.…”
Section: Discussionmentioning
confidence: 74%
“…Observational and experimental studies have demonstrated that hypoglycaemia results in a prolonged QT interval and an increased QT dispersion in healthy individuals and in patients with type 1 and type 2 diabetes [3][4][5][6][7][8][9]. This may partly explain the proarrhythmic effects of hypoglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in either healthy subjects or (type 1 and 2) diabetic patients have investigated the effect of hypoglycaemia on the QT interval. Marques et al [23] and Lee et al [24] have demonstrated a significant QTc prolongation during hypoglycaemia episodes in patients with type 1 diabetes mellitus, and other investigators have found consistent results [25,26] .…”
Section: Hypoglycaemia and The Qt Intervalmentioning
confidence: 77%
“…Not only QTc interval prolongation has a significant impact on hypoglycemia, but an increase in heart rate (HR) also may influence the onset of hypoglycemia. A summary of the mean QTc lengthening during hypoglycemia [23], [24], [25], [26], [27], [28], [29] is shown in Table. I. It can be distantly seen that all the techniques produce a highly significant change of QTc for euglycemia and hypoglycemia conditions.…”
Section: A Electrocardiography (Ecg)mentioning
confidence: 99%